Differential effects of driver sleepiness and sleep inertia on driving behavior. (October 2021) - Wörle, Johanna; Metz, Barbara; Steinborn, Michael B.; Huestegge, Lynn; Baumann, Martin
Highlights : Differential effects of alertness, sleepiness and post-sleep inertia on driving behavior are compared in a simulated 10-min driving task. Lane- and speed-keeping is unstable for drivers under the state of sleepiness and sleep inertia. After napping, lane-keeping performance recovers rapidly while no recovery is evident under the state of sleepiness. Under the state of sleep inertia, drivers compensate for impairments by reducing driving speed. No such compensation is evident for drivers under the state of sleepiness. Performance decrements after awakening have to be taken into account when designing automated driving technology. Abstract: Objectives: Driver sleepiness is one of the major safety issues in conventional driving and sleep inertia emerges as a driver state in automated driving. The aim of the present study was to assess the differential impacts of sleepiness and sleep inertia on driving behavior. Method: 61 participants completed a 10-min manual driving task during an otherwise automated drive. They completed the task (a) under an alert state, (b) under a sleepy state, and (c) after EEG-confirmed sleep. Driving performance was assessed with the parameters lane-keeping, speed choice, and speed-keeping. The eye-blink-based sleepiness measure PERCLOS (the proportion of time with eyes closed) was compared for the three driver states. Results: Lane- and speed-keeping performance were impaired under the sleepy state and after sleep, relative to the alert state. After sleep, lane-keeping behavior recovered rapidly and speed-keeping recovered by trend. Under the sleepy state, performance deteriorated. After sleep, the mean speed was lower than in the sleepy state and in the alert state. PERCLOS was increased after sleep and under the sleepy state, relative to the alert state. Conclusions: Although sleep inertia had detrimental effects on driving parameters similar to sleepiness, this effect rapidly vanished. Hence, while brief naps might be suitable to restore alertness in general, the minimal time needed to regain full capacity after napping should be a focus of future research.